Clinicopathologic Diagnosis of Differentiated Vulvar Intraepithelial Neoplasia and Vulvar Aberrant Maturation. Issue 4 (October 2020) - Day, Tania; Marzol, Alexandra; Pagano, Ross; Jaaback, Ken; Scurry, James
Abstract : Objective: The aim of the study was to describe the demographic, clinical, and histopathologic features of differentiated vulvar intraepithelial neoplasia (dVIN) and vulvar aberrant maturation (VAM). Methods: Specimens from 2010 to 2020 reported as dVIN or VAM were reviewed. Clinical data included age, rurality, symptoms, and evidence of lichen sclerosus (LS). Histopathologic data included epithelial thickness, keratinization, architectural and dyskeratotic features, stroma, p16, and p53. Differentiated vulvar intraepithelial neoplasia and VAM were distinguished by assessment of basal nuclear chromatin, enlargement, pleomorphism, and mitoses. Results: One hundred twenty women with a median age of 71 years had 179 examples of dVIN and VAM. Squamous cell carcinoma was concurrent in 66% and associated with rurality. Ten percent were asymptomatic, and all but 3 had evidence of LS. Differentiated vulvar intraepithelial neoplasia showed a range of thickness, architecture, and dyskeratosis; its unifying !feature was basal atypia. Differentiated vulvar intraepithelial neoplasia displayed hyperchromasia in 83% and easily observed mitoses in 70%. Nonkeratinizing morphology, subcategorized into basaloid and intermediate, occurred in 24% of women with dVIN. Traditional dVIN represented 62% of keratinizing cases; the remainder were atrophic (13%), hypertrophic (13%), acantholytic (8%), or subtle (5%). Vulvar aberrant maturation had abnormal stratum corneum, acanthosis, premature maturation, and enlarged vesicular nuclei. Null p53 helped distinguish dVIN from VAM and dermatoses. Conclusions: The morphology of dVIN encompasses nonkeratinizing and keratinizing types, the latter subdivided into traditional, acantholytic, atrophic, hypertrophic, and subtle. Diagnosis relies on basal atypia with supportive p16 and p53. Atypia exists on a biologic spectrum with mild abnormalities of VAM and reactive change. Identification of dVIN and VAM requires collaboration between clinicians and pathologists experienced in vulvar disorders. Abstract : Supplemental digital content is available in the text.